Teachers Understanding of HOTS Based Assessment in Elementary Schools - Suratmi, Suratmi; Laihat, Laihat; Asnimar, Asnimar; Handini, Ela Okta (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to describe the teachers' understanding of ratings-based thinking higher-order skills (HOTS) in teaching elementary school in the city of Palembang. This research is a qualitative descriptive study. The subject of research is a teacher with a class VI elementary School in the city of Palembang, amounting to 8 people. The research instrument used was a questionnaire. The results showed that an understanding of elementary school teachers in both Palembang city on the already excellent ratings. But understanding the teacher assessment and application of Assessment based on HOTS is still lacking. Teachers have difficulty composing Assessment based on HOTS instrument for learning in elementary schools. Based on the results of this study need to be developed guidelines to develop instruments assessment based on HOTS learning in elementary schools